Dyslipidemia, Physical Activity, and Long Suffering from DM are Associated with Peripheral Neuropathy in Diabetes Mellitus Patients: Cross-Sectional Study: Dyslipidemia, Physical Activity - Heltty, Heltty; Zahalim, Zahalim; Dina, Hasniah (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: DM is a serious problem with the incidence rate increasing every year. Based on data obtained from the Ranomeeto Community Health Center, there are still many DM sufferers found. The results of interviews with residents suffering from DM revealed that there were DM patients who experienced peripheral neuropathy which was characterized by permanent numbness, temporary numbness, and weakness in the legs, namely numbness and cramps. The aim of this research aims to determine the factors associated with the incidence of peripheral neuropathy in diabetes mellitus sufferers in the Ranomeeto Health Center Work Area. Methods: The research method used was observational using a cross-sectional design with a proportional random sampling technique with a population of 215 respondents and a sample size of 68 respondents. Results: The results of the study showed that there was a relationship between the duration of DM and peripheral neuropathy (X2 Calculation = 45.634 ≥ X2 Table = 3.841), there is a relationship between dyslipidemia and peripheral neuropathy (X2 Calculation = 14.645 ≥ X2 Table = 3.841), and there is a relationship between physical activity and the incidence of peripheral neuropathy (X2 Calculation = 39.151 ≥ X2 Table = 3.841). Conclusions: Based on the result, it can be concluded that long suffering from DM, dyslipidemia, and physical activity are factors related to the incidence of peripheral neuropathy in diabetes mellitus patients in the Ranomeeto Health Center Working Area.